RANCANG BANGUN SMARTHOME BERBASIS HAIWELL CLOUD SCADA MENGGUNAKAN ESP32 - Muhammad Rifky Al Faris; Denny Irawan (E-Link: Jurnal Teknik Elektro dan Informatika, 2024)
These days, there is a definite need for labor that is quicker, simpler, and more succinct as technology advances. The term "smart home" refers to a technology or device concept that integrates electronic devices and household equipment for monitoring and control. This allows all of the devices in the house to be monitored and controlled centrally in a central microcontroller, specifically a microcontroller that can be controlled remotely in real time. In this project, the author controls electronic items including lights, fans, and televisions using a relay. After determining the room's temperature using a temperature and humidity sensor (the DHT22), it links the sensor to a fan to gradually lower the room's temperature. PZEM-004T sensor for power, voltage, and current measurement and control. The lights on the house's terrace are controlled by the LDR sensor, also known as a light sensor. The ESP32 microcontroller integrates and connects everything, while Haiwell Cloud Scada controls and monitors it all.